Coprecipitation technique to prepare BaNb2O6 - Natarajan, N; Samuel, V; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and niobium ions as barium oxalate and niobium hydroxide under basic conditions. This precursor on calcination at 750degreesC yielded BaNb2O6 ceramics. This is a much lower temperature as compared to that prepared by traditional solid-state method (1000degreesC), as reported for the formation of BaNb2O6. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ammonia; Ceramics; Electron microscopy; niobium oxide; Oxides

Preparation of nanocrystalline ferroelectric CaBi2Ta2O9 by the urea method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Ceramics International, 2005)
A precipitate was formed when a aqueous solution of CaCl2, BiCl3, TaF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath. This precipitate on decomposition at 600 degrees C yielded the nanocrystallites of ternary oxide CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) were also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 70 nm. The room temperature dielectric constant was found to be 110. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders : chemical preparation

Preparation of nanocrystalline ferroelectric CaBi2TaO9 by citrate gel method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A gel was formed when an aqueous solution of CaCl2, BiCl3, TaF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600degreesC yielded the nano-crystallites of ternary oxide, CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) are also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 40 nm. The room temperature dielectric constant was found to be 90. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Bismuth; diffraction; Electron microscopy

Preparation of nanocrystalline MgNb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Letters, 2005)
A gel was formed when a aqueous solution of Mg(NO3)(2), NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, MgNb2O6 (MN). The formation of MN phase and lattice parameters were determined by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Electron microscopy; magnesium niobate; powders; X-ray diffraction

Synthesis of nanocrystalline rutile - Samuel, V; Pasricha, R; Ravi, V (Ceramics International, 2005)
Nanocrystalline titanium dioxide (TiO2) in the rutile phase has been obtained by homogeneous precipitation using urea and TiOCl2. A mixture of urea and TiOCl2 is heated on a hot water bath at 65-75 degrees C to precipitate rutile powders. X-ray diffraction (XRD) studies on these oven-dried powders indicated the formation of single-phase rutile. Raman scattering experiments were also performed to confirm the formation of the rutile phase. Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 40 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; Electron microscopy; powders; TiO2; X-ray methods

Synthesis of Sr0.5Ba0.5Nb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Chemistry and Physics, 2005)
A gel was formed when an aqueous solution of BaCl2, SrCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at I kHz is 1000. The ferroelectric hysteresis loop parameters of these samples were also studied by a home built Sawyer-Tower circuit. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides